ESENSI PENDIDIKAN ONTOLOGIS HEIDEGGER BAGI PENDIDIKAN TINGGI - Sudarto Murtaufiq; Ahmad Hanif Fahruddin (Universitas Islam Lamongan, 2019)
This paper is aimed at examining the Heidegger's ideas in dealing with the current crisis in higher education. Such issues as instrumentalization, professionalization, vocationalization, and technologization in today's modern university have resulted in the increasing hyper-specialization and ruinous fragmentation of its all aspects. On this stand, Heidegger offers an ontological conception of education that is purposefully capable of bringing about a renaissance of the university. Inspired by the Plato’s popular ‘allegory of the cave’, Heidegger both excavates and appropriates the original Western educational ideal of Platonic paideia. In addition, The Heidegger's notion of ontological education could be considered as a philosophical perfectionism, a re-essentialization of the currently empty ideal of educational ‘excellence’ by which Heidegger believes we can reconnect teaching to research and, ultimately, reunify and revitalize the university itself.